Visualization of Component Status Information of Prefabricated Concrete Building Based on Building Information Modeling and Radio Frequency Identification: A Case Study in China - Guofeng Ma; Jun Jiang; Shanshan Shang (Advances in Civil Engineering)
In view of the problems such as the basic properties, usage, and location of prefabricated concrete building components, which are easy to be omitted, missed, and difficult to query in the field management, this study introduces building information modeling (BIM) and radio frequency identification (RFID) technologies to visualize the state information of prefabricated concrete components, such as component type, manufacturer, location, and temperature. In the design stage, a new RFID family can be built in the actual model in order to solve the lack of definition of RFID family through the Industry Foundation Class (IFC) standard, and the databases of BIM and RFID can be connected with C# language, realizing the effective integration of the two engineering technologies. In the application stage, through the secondary development of Revit, the information connection between PC terminal and RFID equipment is completed, and the component data collected by RFID tags are transmitted to the BIM model to realize the integration and visualization of prefabricated component state information. In this study, the traceability of prefabricated components of prefabricated concrete buildings can be improved, providing a basis for quality responsibility tracking in the later period, reducing unnecessary waste of human and material resources and helping to maximize economic benefits.